(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Introduction: Coronaviruses are a broad group of viruses that can infect both humans and animals and make them sick. In mid-December 2019, a seafood market in Wuhan, China’s Hubei Province, reported an outbreak of the novel coronavirus illness (COVID-19), which later expanded to 214 other nations, territories, and regions. A respiratory tract illness linked to SARS-CoV-2 infection is what the majority of COVID-19 patients primarily experience. A few patients with severe COVID-19 infections also frequently display coagulation problems, which are linked to respiratory decline and death. Additionally, many COVID-19 patients experience thromboembolic issues that appear to be connected to the coagulopathy. Material and Methods: The site of this study was a tertiary care hospital that was also designated as a Level 3 institution for the care of Covid 19 patients. A semi-automated coagulation analyzer (Coag 2D) was used to perform the following tests: platelet count, Prothrombin time (PT), activated partial thromboplastin time (APTT), fibrinogen, and Ddimer tests. The coagulation parameters at admission and later during the hospital stay were compared between the survivors and non-survivors group. Result: A substantial coagulation disorder appears to be brought on by severe COVID-19 infections. In patients with severe COVID-19, an unusually high D-dimer result is the most obvious coagulation test anomaly. Nearly 40.9% of patients in the current study had D-dimer levels that were noticeably elevated, and 100% of the patients in the severe non-survivor category also had D-dimer levels that were significantly elevated. Conclusion: Coagulation problems are linked to severe COVID-19 infection. It is important to distinguish the coagulopathy caused by COVID-19 from other types of DIC and to classify it as a distinct kind of prothrombotic intravascular coagulation that may require new diagnostic criteria.